THE USERS’ BEHAVIORAL INTENTION TO USE MOBILE HEALTH-TECH APPLICATION TO PREVENT THE SPREADING OF CORONAVIRUS (The South East European Journal of Economics and Business, 2022)
The emergence of mobile health applications (MH-Apps) has enhanced the healthcare field’s services, particularly in the treatment, diagnosis, and follow-up. AMAN Mobile Health Application (AMAN MH-App) is one of the health-tech solutions used to fight the Coronavirus pandemic. It has a built-in feature to track users’ activities to protect users from contacting an infected person. However, the acceptance of AMAN MH-App in Jordan is still in an early stage, and the number of users has reached 15% of the country’s population. Therefore, this study aims to assess the use of AMAN MH-App among young people using the quantitative method. A total of (450) valid samples participated in the study after removing 33 invalid samples. Smart- PLS 3.2.7 was used for data analysis. The findings showed that all independent variables (Perceived useful- ness, Perceived ease of use value, Subjective norms, Perceived behavioral control, Information Credibility, and Optimism) positively impact on the dependent variable (Behavioural Intention to use AMAN MH-App). We believe that AMAN MH-App’s information’s credibility (i.e. providing up-to-date, authoritative, accurate, and trustworthy information) will increase the number of the App’s users. The results of this research can be ap- plied to similar context and applications in different countries.